Bank selection criteria in the banking industry: An empirical investigation from customers in Romanian cities - Katircioglu, Salih Turan; Tumer, Mustafa; Kilinc, Ceyhun (Academic Journals, 2011)
The present study investigates bank selection criteria of customers in Romania. A total of 248 bank customers responded to the bank selection instrument in two main cities of Romania: Bucharest and Constanta. The number of ATM (automatic teller machines) booths has been found to be the most important selection criteria for bank customers from Romania. This study has also shown that providing extensive ATM services, availability of telephone and internet banking, giving personal attention to customers, reputation and image of the banks, confidentiality of the bank for customer records, appearance of staff to be presentable and the number of branch offices around the country are all the most important factors that Romanian people give attention to. Finally, the results of this study have also shown that Romanian people give little attention to mass media advertisement, gifts provided by banks, fast and efficient service and recommendation by other people in their environment. Finally, bank selection criteria statistically differ across cities and income levels in Romania. This shows that people in different cities and in different income groups have different preferences of bank selection criteria in Romania.
Keywords: Banking industry; bank selection; criteria; Romania